FAMILY FRIENDLY FOR IMPROVEMENT OF USING EXCLUSIVE BREAST WITH INTEGRATION FAMILY CENTER NURSING MODEL AND TRANSCULTURAL NURSING MODEL AT JEMBER DISTRICT, EAST JAVA PROVIENCE - Tantut Susanto; Lantin Sulistyorini (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2014)
Introduction. The phenomenon of lactation in nursing mothers breastfed exclusively fulfillment requires comprehensive treatment in the community related to the population at risk in the group of breast feeding mothers in the community. The purpose of this study was to improve the ability of nursing mothers, families, and communities in family friendly activities through the integration of family center model of cross-cultural nursing and nursing to meet the sustainability of exclusive breastfeeding in the group of nursing mothers who were sensitive and sensitive to local culture in Jember. Method. This study used a quasi- experimental design with a nonrandomized control group design with pretest and posttest. The data were analyzed using frequency distributions and the Wilcoxon signed rank test were used to compare the behavior of lactating mothers, family independence, the ability of health workers, and management of exclusive breastfeeding services are culturally sensitive and locally sensitive to the treatment group and the control group. Results. The results showed no significant difference between the behavior of lactating mothers, family independence, and management services exclusive breastfeeding before san after the intervention program (p value 0.000) and no significant difference between the ability of health workers before and after the intervention (p value 0.001). Discussion. Exclusive breast feeding can run continuously if the full support of breastfeeding mothers own motivation, family support, health worker visits, and the clinic. Keywords: Exclusive Breast Feeding, Family Friendly, Mother’s Behavior, Cadre Capability.